POTENTIAL UTILIZATION IN DYE DECOLORIZATION OF SPENT MUSHROOM SUBSTRATES - Kang, Hee-Wan (International Journal of Biosciences and Biotechnology; Vol 3 No 2 (2016), 2016)
Pleurotus ostreatus, P. eryngii, and Flammulina velutipes are main edible mushrooms that account forover 89% of total mushroom production in Korea. Of them, cultivation of P. eryngii is 25%. About 2.5million tons of spent mushroom substrate (SMS) is produced each year in Korea. It is either used asgarden fertilizer or deposited in landfills, which pollutes the environment. This study was carried out toextract the lignocellulolytic enzymes amylase (EC 3.2.1.1), cellulase (EC 3.2.1.4), laccase (EC 1.10.3.2),and xylanase (EC 3.2.1.8) were efficiently extracted from spent mushroom substrate (SMS) of ediblemushrooms. laccase activity were highest in extracts from the P. eryngii SMS, with values of 8.01 U/g.The synthetic dyes remazol brilliant blue R and Congo red were decolorized over 88 and 93% by thewater extract of P. eryngii SMS within 120 min, and the extract’s decolorization ability was compared tocommercial laccase. Furthermore, the SMS extract was applied to decolorize textile mill wastewater dyefor its industrial application.
Keywords: Decolorization; Spent mushroom substrate; Water extract